Sexual Dimorphism of the Heart: Genetics, Epigenetics, and Development - Deegan, Daniel F.; Nigam, Priya; Engel, Nora (Frontiers in Cardiovascular Medicine, 2021)
The democratization of genomic technologies has revealed profound sex biases in expression patterns in every adult tissue, even in organs with no conspicuous differences, such as the heart. With the increasing awareness of the disparities in cardiac pathophysiology between males and females, there are exciting opportunities to explore how sex differences in the heart are established developmentally. Although sexual dimorphism is traditionally attributed to hormonal influence, expression and epigenetic sex biases observed in early cardiac development can only be accounted for by the difference in sex chromosome composition, i.e., XX in females and XY in males. In fact, genes linked to the X and Y chromosomes, many of which encode regulatory factors, are expressed in cardiac progenitor cells and at every subsequent developmental stage. The effect of the sex chromosome composition may explain why many congenital heart defects originating before gonad formation exhibit sex biases in presentation, mortality and morbidity. Some transcriptional and epigenetic sex biases established soon after fertilization persist in cardiac lineages, suggesting that early epigenetic events are perpetuated beyond early embryogenesis. Importantly, when sex hormones begin to circulate, they encounter a cardiac genome that is already functionally distinct between the sexes. Thus, both the sex chromosomes and sex hormones contribute to differences between male and female hearts. We explore the possibility that sexual dimorphism of the developing heart predicts sex-specific responses to environmental signals and foreshadows sex-biased health-related outcomes after birth.